The Role of the Tropical Indian Ocean in Global Climate - Bader, Jürgen (Staats- und Universitätsbibliothek Hamburg Carl von Ossietzky, 2005)
Among the most striking decadal climatic trends of the last century are the strengthening of the NAO index and the decreasing summer monsoon rainfall over sub-Saharan West Africa. This thesis focuses on the role of tropical sea surface temperatures (SSTs) driving theses changes. Both of these changes are investigated by conducting experiments with the atmospheric general circulation model ECHAM4.5 - run in stand-alone mode - and the global ocean-atmosphere-sea ice model MPI-OM/ECHAM5. These experiments provide evidence that the Indian Ocean warming in the last decades is of paramount importance in driving the recent observed drying trend over the West Sahel. The model West Sahel dried more when tropical seas were warmer during the past half-century than when they were cooler. When sea surface temperatures were changed in one ocean basin at a time, it was the tropical Indian Ocean that dominated. The warming of the Indian Ocean produces through atmospheric teleconnections mid-tropospheric large-scale subsidence over sub-Saharan West Africa. The Indian and eastern tropical Atlantic Oceans are key ocean areas for driving the two basic rainfall anomaly patterns over sub-Saharan West Africa in summer. This could improve the ability to predict sub-Saharan West African rainfall variability on interannual time-scales. It is found further that the progressive warming of the tropical Indian Ocean is a principal contributor to the strengthening of the North Atlantic Oscillation via the jet stream waveguide.